2023
DOI: 10.3390/microorganisms11082073
|View full text |Cite
|
Sign up to set email alerts
|

Early Fluvoxamine Reduces the Risk for Clinical Deterioration in Symptomatic Outpatients with COVID-19: A Real-World, Retrospective, before–after Analysis

Abstract: Fluvoxamine, a selective serotonin reuptake inhibitor with anti-inflammatory properties, has gained attention as a repurposed drug to treat COVID-19. We aimed to explore the potential benefit of fluvoxamine on outpatients with early SARS-CoV-2 infection. We performed a retrospective study of fluvoxamine adult outpatients with symptomatic COVID-19 disease of early onset (<5 days), in the context of an infectious diseases private practice, between September–December 2021, in Greece. Patients with disease dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…All the studies identified for this meta-study scored one or higher and were therefore deemed eligible for meta-analysis. Four of the studies scored below five 28 , 29 , 32 , 35 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…All the studies identified for this meta-study scored one or higher and were therefore deemed eligible for meta-analysis. Four of the studies scored below five 28 , 29 , 32 , 35 .…”
Section: Resultsmentioning
confidence: 98%
“…A Ugandan study of fluvoxamine showed that it was significantly associated with reduced mortality but did not decrease time spent in hospital 31 . A small open-label study in Greece investigated fluvoxamine as part of a real-world, retrospective, before–after analysis, and the results also indicated that it reduced the risk of clinical deterioration in COVID-patients (3.8% of fluvoxamine-treated patients and 16% standard care patients experienced clinical deterioration (OR 0.12; 95% CI 0.02–0.70, p < 0.02) 32 .…”
Section: Resultsmentioning
confidence: 98%
“… [46] , [47] , [48] Similarly, several, [49] , [45] though not all [50] , [51] , [52] prospective, randomized, controlled investigations into the potential therapeutic effects of fluvoxamine in outpatients with acute COVID-19, have suggested evidence of benefit. A number of other investigators have been interested in the evaluating whether SSRIs prevent COVID-19, exert a treatment effect in acute infection or lower early mortality after acute COVID-19 [53] , [54] , [55] , [56] , [57] , and a recent uncontrolled study including 95 patients with PASC treated with SSRI therapy has been published [58] , but to our knowledge, ours is the first study to suggest a diminished risk of the development of Long COVID in patients receiving SSRIs at baseline (i.e., prior to SARS-CoV-2 infection). Although an immunological basis for this observation has been postulated, we acknowledge the possibility that the findings in the current study may reflect non-immunological effects of SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by the results of a large retrospective study exploring the effects of AD on COVID-19 severity and mortality ( N = 25 034) ( 4 ). Also bearing in mind the assumed mechanisms of action, which make the major effect in particular at the beginning of the infection plausible, the current evidence suggests that the earlier the AD were administered to patients exposed to SARS-CoV-2 or showing first mild-to-moderate COVID-19 symptoms, the more favorable was the outcome regarding SARS-CoV-2 infection rates, COVID-19 severity and related mortality ( 7 , 17 ). On the other hand, AD seemed to have no relevant impact when they were added to the standard treatment of a full-blown COVID-19 pneumonia ( Table 1 ) ( 8 , 11 ).…”
Section: Controlled Clinical Studiesmentioning
confidence: 95%